1×9+{7×[6-(4+2×3)÷5]-8}÷10=11
Răspunsuri la întrebare
Răspuns de
0
Răspuns:
1×9+[7×(6-10÷5)-8]÷10=11
1×9+(7×4-8)÷10=11
1×9+20÷10=11
9+2=11
11=11,,A"
Răspuns de
1
Răspuns:
Explicație pas cu pas:
1×9+{7×[6-(4+2×3)÷5]-8}÷10=11
1×9+{7×[6-(4+6)÷5]-8}÷10=11
1×9+[7×(6-10÷5)-8]÷10=11
1×9+[7×(6-2)-8]÷10=11
1×9+(7×4-8)÷10=11
1×9+(28-8)÷10=11
1×9+20÷10=11
9+2=11
11=11 qed
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Chimie,
8 ani în urmă
Biologie,
9 ani în urmă
Matematică,
9 ani în urmă